Nitric Oxide Synthase activity in major depressive episodes before and after antidepressant treatment: Results of a large case-control treatment study. Issue 1 (11th January 2022) - Loeb, E.; El Asmar, K.; Trabado, S.; Gressier, F.; Colle, R.; Rigal, A.; Martin, S.; Verstuyft, C.; Fève, B.; Chanson, P.; Becquemont, L.; Corruble, E.
Abstract: Background: Nitric oxide synthase (NOS) activity, an enzyme potentially involved in the major depressive episodes (MDE), could be indirectly measured by the L-Citrulline/L-Arginine ratio (L-Cit/L-Arg). The aim of this study was: (1) to compare the NOS activity of patients with a MDE to that of healthy controls (HC); (2) to assess its change after antidepressant treatment. Methods: A total of 460 patients with a current MDE in a context of major depressive disorder (MDD) were compared to 895 HC for NOS activity (L-Cit/L-Arg plasma ratio). L-Arg and L-Cit plasma levels were measured using a MS-based liquid chromatography method. Depressed patients were assessed at baseline, and after 3 and 6 months of antidepressant treatment for depression severity and clinical response. Results: Depressed patients had a lower NOS activity than HC at baseline [0.31 ± 0.09 v. 0.38 ± 0.12; 95% confidence interval (CI) −0.084 to −0.062, p < 0.0001]. Lower NOS activity at baseline predicted a higher response rate [odds ratio (OR) = 29.20; 95% CI 1.58–536.37; p = 0.023]. NOS activity in depressed patients increased significantly up to 0.34 ± 0.08 after antidepressant treatment (Est = 0.0034; 95% CI 0.0002–0.0067; p = 0.03). Conclusions: Depressed patients have a decreased NOS activity that improves after antidepressant treatment and predicts drug response. NOS activity may be a promising biomarker for MDE in a context of MDD.